A pancake-resolver model for sensor manufacturers. (28th November 2011) - Figueiredo, Jo?o Manuel Gouveia
A sensor?s model for resolver manufacturers is developed. This model compensates deviations in product characteristics due to the variability of the assembly process, through computed corrections on the production?s controllable variables ? ewinding parameters. The model follows a two-step strategy. On the first step a traditional transformer?s model computes the resolver?s nominal physical parameters: electric and magnetic resistances and leakage impedances of primary and secondary windings. On the second step a linear model computes the increments on the controllable variables to compensate small deviations in design assumptions, due to the variability of the manufacturing processes. In this model the in-plant controllable variables are adjusted (number of windings and wire diameters). The incremental model develops a set of correction tools that allows the resolver manufacturer to change some controllable variables in order to correct assembled resolvers that without any action would be scrap to the production line.